Everolimus for the treatment of advanced pancreatic neuroendocrine tumors. (November 2012) - Tomassetti, Paola; Cevenini, Monica; Guidetti, Elena; Cacciari, Giulia; Cipollini, Maria Luigia; Galassi, Eleonora; Fabbri, Maria Camilla; Nori, Francesca; Campana, Davide; Corinaldesi, Roberto; De Giorgio, Roberto
Pancreatic neuroendocrine tumors (pNETs) account for 1–2% of all pancreatic tumors. Approximately two-thirds of patients have an advanced disease with metastases at diagnosis. Surgery is still the gold-standard treatment in most cases, while few medical options exist for inoperable tumors. A new potential therapeutic approach for advanced pNETs results from targeting intracellular molecular pathways. Rapalogs – rapamycin analogs including everolimus – target the mTOR signaling cascade, inhibit cell proliferation and evoke apoptosis. Recent Phase II and III clinical trials demonstrated that everolimus is effective in advanced pNETs as it increases progression-free survival of treated patients. Everolimus appears to be promising for advanced pNETs and is usually tolerated with mainly mild adverse events. Future studies will establish whether everolimus, alone or in combination with other compounds (e.g., new somatostatin analogs, cytotoxic agents and anti-angiogenetic drugs), will also prove to be a valid option for patients with other forms of advanced neuroendocrine tumors.